Trend in Short-Duration Extreme Precipitation in Hong Kong - Yu, Lejiang; Zhong, Shiyuan; Qiu, Yubao; Liang, Xi (Frontiers in Environmental Science, 2020)
This study examines trends in the intensity and frequency of short-duration (5 min to 3 h) rainfall extremes in Hong Kong for the period of 1984 to 2010 and the drivers for the trends using gauge observations and gridded reanalysis. Both the intensity and frequency of rainfall extremes exhibit an upward trend, with the slope for the intensity (frequency) trend increasing (decreasing) as duration lengthens from 5 min to 3 h. The upward intensity (frequency) trends appear to be a manifestation of an abrupt change around 1991/1992 (1992/1993) that separates a period of lower and fewer rainfall extremes before from a period of higher and more extremes after. The increase in Hong Kong’s extreme rainfall after the early 1990s is likely caused by a combination of stronger rising motion along Southeast China Coasts and enhanced moisture transport into South China Sea resulting from the strengthening and westward shift of the western Pacific subtropical high associated with anomalous convective activities over the tropical western Indian Ocean and a positive phase circumglobal teleconnection wavetrain.